A dynamic model of simultaneous price competition with switching and search costs - Guthmann, Rafael Roos (2013)
This paper presents a dynamic model of price competition that incorporates both switching and search costs and where the consumer's and rms' decisions are simultaneous. Given the assumptions made we see that this model has an equilibrium. The main properties of the equilibrium of the model are: If search costs are low enough in equilibrium consumer will search all rms in the market while increasing search costs will decrease the proportion of rms being searched. A counterintuitive result is that the expected prices paid by the consumer usually decrease in our numerical computations of equilibrium when search costs increase. While increasing switching costs will also produce the counterintuitive result that unmatched rms will decrease their price o ers in order to attract the consumer.